2012
DOI: 10.1007/s10637-012-9831-9
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of vorinostat and MLN8237 in pediatric leukemia, medulloblastoma, and neuroblastoma cell lines

Abstract: Summary Purpose Histone deacetylase (HDAC) inhibitors, such as vorinostat, decrease Aurora kinase activity by a variety of mechanisms. Vorinostat and MLN8237, a selective Aurora A kinase inhibitor, disrupt the spindle assembly and the mitotic checkpoint at different points, suggesting that the combination could have increased antitumor activity. The purpose of this study was to determine the cytotoxicity of vorinostat and MLN8237 in pediatric tumor cell lines. Methods Cell survival was measured after 72 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Our data demonstrate that the combination of BI-2536 or VX-680 with chemotherapeutic agents (Vincristine, Cisplatin, or Cyclophosphamide) or radiation is more effective than chemotherapy or radiation alone. Previous studies have shown similar effects of combined treatment of established MB cell lines with chemotherapy or radiation plus Aurk or Plk inhibitors (5153). Together, these studies suggest that incorporating Aurk or Plk inhibitors into MB therapy might enable a reduction in the doses of chemotherapy/radiotherapy and thereby reduce the long-term side-effects associated with these treatments.…”
Section: Discussionmentioning
confidence: 73%
“…Our data demonstrate that the combination of BI-2536 or VX-680 with chemotherapeutic agents (Vincristine, Cisplatin, or Cyclophosphamide) or radiation is more effective than chemotherapy or radiation alone. Previous studies have shown similar effects of combined treatment of established MB cell lines with chemotherapy or radiation plus Aurk or Plk inhibitors (5153). Together, these studies suggest that incorporating Aurk or Plk inhibitors into MB therapy might enable a reduction in the doses of chemotherapy/radiotherapy and thereby reduce the long-term side-effects associated with these treatments.…”
Section: Discussionmentioning
confidence: 73%
“…Alisertib synergizes with vorinostat in vitro in pediatric leukemia, medulloblastoma, and neuroblastoma cell lines. (43). …”
Section: Aurora Kinase Inhibitionmentioning
confidence: 99%
“…Specifically, MLN8237 is a second generation, orally bioavailable, selective AURKA inhibitor that has been shown to induce cytotoxicity and cell cycle arrest in multiple myeloma (11), enhance chemosensitivity in esophageal cancer, medulloblastoma, and neuroblastoma (12, 13). Preclinical studies using MLN8237 showed significant in vitro growth inhibition and a positive impact on in vivo event-free survival in several pediatric cancers, including neuroblastoma (14), thus prompting phase I clinical trials (15).…”
Section: Introductionmentioning
confidence: 99%